Effect Of Ice Compress On Pain Response To Pentabio Immunization In Underwears At Puskesmas Deleng Pokhisen Year 2021 - Indra Agussamad; Nur Afiqah Mohamad; Adelina Sembiring; Ester Simanulang; Eli Aisah Tamba; Julius Daud Nduru (Sean Institute, 2021)
Children who are immunized with Pentabio will experience pain which can cause excessive anxiety and even trauma. One method of reducing pain is an ice pack. However, currently there are not many ways used to reduce pain during immunization. The purpose of this study was to determine whether there was an effect of applying ice packs to the pain response during Pentabio immunization in toddlers. This type of research is a quasi-experimental post-test only with group control design. The experimental group was treated with ice packs before immunization, while the control group was given the distraction treatment. The sample size in this study was 50 respondents selected by purposive sampling technique and tested using the t-test. Based on the results of the t-test, in the control group there were 14 children who experienced very severe pain, while in the experimental group there were 4 children who did not experience pain. The difference in pain levels between the two groups obtained a p value of 0.0001 (0.0001 <0.05). It is recommended that there be the latest policies regarding immunization to improve the quality of services related to reducing pain when children are immunized. It is hoped that the community, including parents, will no longer be afraid of immunizing their children because there is an ice pack technique that can reduce pain when immunization is carried out, so that children can feel more comfortable with an easy, cheap and safe method.